Design of a low-voltage CMOS rail-to-rail op amp - Guo, Dianbo. (2008)
The aim of this project is to design a low-voltage rail-to-rail fully differential operational amplifier. The application of such a circuit is for portable electronic devices, which make use of only one battery cell. The circuit will be designed and simulated using a series of Mentor Graphics software. The process used is 0.6um single P-well CMOS process of Austria Mikro Systeme International (AMS).